The experimental study of shallow flows of liquid on the airport runways and automobile roads - Beljatynskij, Andrey; Prentkovskis, Olegas; Krivenko, Julij (Transport, 2010)
Hydroplaning or aquaplaning is associated with the complete loss of the grip of a tyre because of the presence of a water film between the tyres of a moving vehicle (an automobile, an airplane, etc.) and the road surface. In this case, a vehicle becomes uncontrollable. Hydroplaning (aquaplaning) occurs when the speed of a vehicle reaches the critical value, when the wheel does not have time enough for water compulsion, which leads to the formation of a permanent water film between it and the road surface. The higher the depth of the water on the road surface under the tyre, the higher the risk of hydroplaning (aquaplaning). In other words, hydroplaning (aquaplaning) is the floating of the wheel on the water wedge. In physical terms, it is the loss of the ability of a tyre of the effective water compulsion from the contact area with the road. As a result, a water film of several millimeters is formed under the wheel, and a vehicle actually floats up. The article presents the results obtained in the experimental study of the flows of liquid, whose depth is comparable with that of depressions and cambers of rough roadway pavement. It is stated that the relationships used for calculating surface flows should be corrected for shallow flows, taking into account the actual roughness of road covering. Shallow flows are mostly laminar. The transition Reynolds numbers are about 3000. The relationships used for calculating shallow flows may be determined more accurately by test pouring of water on the surface of roadway pavement, with further generalization of the data. The experimental research performed is closely related to the study of the problems of aquaplaning and traffic safety of various means of transport.First published online: 10 Feb 2011